Prevenção dos efeitos tóxicos do cloreto de mercúrio em ratos jovens pelo cloreto de zinco: papel das metalotioneínas - Peixoto, Nilce Coelho (2006)
Zinc, cadmium, and mercury are divalent metals and constitute same group of the periodic table. While zinc is an essential metal, the others are toxic metals. The most important common feature among these metals is the ability to induce the synthesis of metallothioneins (MT), which occurs in two vital organs involved in detoxification, the liver and kidney. The main role of MT is the detoxification of heavy metals and the regulation of homeostasis of essential trace metals, such as copper and zinc. There are several studies about mercury toxicity and the role of MT in adult animals. However, the sensitivity of developing animals to various compounds differs from that observed in adults and may to related to different posnatal phases of the development. The aim of this investigation was to verify the effects of CdCl2 and ZnCl2 pretreatments on the deleterious effects of HgCl2 in young rats and to investigate whether MT were involved in this protection mechanism. When pups were three days old, they received five consecutive injections (s.c.) of saline, CdCl2 (3.7 mg/kg/day) or ZnCl2 (27.0 mg/kg/day). On the five subsequent days, the animals were injected daily with one dose (s.c.) of saline or HgCl2 (5.0 mg/kg). Pups were sacrificed 24 h after the last dose and samples were collected (blood, liver and kidneys). The body and renal weights, hepatic and renal porphobilinogen synthase (PBG-synthase) activity, alanine aminotransferase activity, creatinine, urea, glycemia, and the retention of heavy metal in tissues were significantly altered by HgCl2. Prior exposure to CdCl2 prevented the effect of mercury on renal PBG-synthase, but did not alter mercury levels in the tissues. In general, the effects of mercury were prevented or lessened by zinc, except that the zinc pre-treatment increased the retention of mercury in the kidneys and did not modify the increase of renal weight induced by mercury. MT contents were increased by treatments with mercury and zinc and the greatest increase was induced by latter. The metal distribution in subcellular fractions showed that in both the insoluble fraction (IF) and heat treated cytosolic fraction (HTC), the contents were modified by the treatments. Although the HTC fraction is rich in MT, higher zinc and mercury contents were verified in the IF from all tissues analyzed. The relationships between MT and HTC metals showed that in the hepatic and renal tissues whenever there is an increase of metal levels there is increase of MT content. The reduction of hepatic and blood mercury levels and the increase of this metal in the kidneys induced by zinc suggests that the heavy metal contained in the liver is carried to the kidneys through the blood. This process also would transport MT from the liver to the kidneys. Moreover, it is important to emphasize that in cells in proliferation, which occur during rapid growth, there are nuclear and mitochondrial MT. Therefore, the high content of mercury found in the IF, enriched fraction in nucleus and mitochondria, would be bound to MT, as well. Considering that the zinc pretreatment induced an increase of renal MT of around 80% and the group treated with zinc and mercury presented a content of mercury in this protein that was 25% higher than for the group treated only with mercury, these results suggest that MT are, at least in part, responsible for the reduction of the toxicity of mercury seen in the various parameters analyzed in this work.